2009
DOI: 10.1186/1475-2875-8-275
|View full text |Cite
|
Sign up to set email alerts
|

Quality of malaria case management at outpatient health facilities in Angola

Abstract: BackgroundAngola's malaria case-management policy recommends treatment with artemether-lumefantrine (AL). In 2006, AL implementation began in Huambo Province, which involved training health workers (HWs), supervision, delivering AL to health facilities, and improving malaria testing with microscopy and rapid diagnostic tests (RDTs). Implementation was complicated by a policy that was sometimes ambiguous.MethodsFourteen months after implementation began, a cross-sectional survey was conducted in 33 outpatient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
76
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 19 publications
(31 reference statements)
10
76
4
2
Order By: Relevance
“…This persists even when they perform the test themselves and particularly when the results clash with observed signs and symptoms (Kyabayinze et al, 2010;Moonasar et al, 2007;Rowe et al, 2009;Uzochukwu et al, 2010). Results from a recent survey of health facilities in Cameroon in 2009 indicate malaria is significantly overdiagnosed and mistreated (Mangham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This persists even when they perform the test themselves and particularly when the results clash with observed signs and symptoms (Kyabayinze et al, 2010;Moonasar et al, 2007;Rowe et al, 2009;Uzochukwu et al, 2010). Results from a recent survey of health facilities in Cameroon in 2009 indicate malaria is significantly overdiagnosed and mistreated (Mangham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Three years after these guidelines were disseminated, over half of providers continued to treat clinically suspected cases of malaria despite negative laboratory testing. 9 Fever alone is frequently the only clinical criterion for diagnosis, and yet one study showed that only 3.6% of fevers in children under 5 years of age in Luanda, the densely populated urban capital, had a positive malaria diagnostic test. 10 Misdiagnosis results in overrepresentation of the burden of malaria and derails clinical investigation into other, potentially life-threatening, causes of illness.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A consequence of the prolonged neglect of laboratories in malaria case management is that, even when quality laboratory services are available, clinicians too frequently ignore negative results. [7][8][9][10][11][12] The reduction in clinical malaria in several countries [13][14][15][16] and the use of expensive artemisinin-based combination therapeutic (ACT) antimalarial drugs call for case management practices that emphasize parasitologic confirmation, because continued use of ACTs in non-malaria cases represents a waste of resources and eventually, is unsustainable. Indiscriminate use of ACTs could create sufficient drug pressure that hastens development of resistant parasites, a situation that has begun to develop in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%